AB0579 Immune related diffuse alveolar haemorrhage: single center experience and long term outcome – rheumatological perspective. (15th June 2017) - Bindroo, MA; Gupta, R; Mendiratta, N; Raval, D; Ekbote, G; Singal, V
Abstract : Background: Diffuse alveolar haemorrhage (DAH) is a feature of several immune and nonimmune disorders. Failure to diagnose and treat DAH syndromes in their early stages may lead to acute respiratory failure, CKD and death. Prognosis is poor with in-hospital mortality ranging from 20% to 100%. Immune related DAH is monophasic and if treated early and achieved remission, long term outcome is good. Objectives: To evaluate the therapeutic response and long term outcome in patients with Immune related (AAV & SLE) DAH. Methods: A retrospective review of medical records of patients admitted under Rheumatology and Clinical immunology department with Immune related DAH was made with regards to their presentation, treatment & response, mortality, morbidity and long term outcome. Study was performed after approval and ethical clearence from IRB. Results: From June 2012 to Augst 2016, 18 patients (15 were AAV related & 3 as SLE related) were admitted. Amongst AAV patients, PR3 positive were 11 & MPO positive were 4. Fourteen patients were females and 4 males, age ranged from 14 – 68 yrs (median=54.5 yrs). Mean duration of disease before onset of DAH was 3 months. Nine (50%) patients had associated kidney and musculoskeletal involvement. Eleven (61.11%) patients were admitted under ICU care requiring artificial ventilation. Pulse methylprednisolone injections were given in 15 (83.33%), Cyclophosphamide in 13 (72.22%), IVIg in 2 (11.11%), plasmapheresis in 7 (38.88%) patients. Time from first consultation to pulse methylprednisolone was in range from 1 to 5 days. Out of 18, 11 patients achieved remission. In hospital mortality was seen in 5 (27.77%) patients, all were AAV (MPO+=3, PR3+=2), all were complicated with sepsis with MODS before death. Out of 7 who received plasmapheresis, 2 patients (28.4%) died, 2 patients developed CKD (dialysis independent). Duration of ICU& hospital stay in days ranged from 3 to 28 days & 2 to 40 days respectively. Mean follow up was 16 months (range 11–42 months) on OPD visits. Two had relapse on follow up (1 nephritis, 1 persistant cavities with episcleritis) who were given Rituximab. Total 5 (38.46%) received Rituximab out of which 2 were refractory to Cyclophosphamide, 2 had relapse & 1 concomitantly. Eight patients (44.44%) developed morbidity in the form of dialysis independent-CKD in 4 (PR3+ in 2, MPO+ in 1 and Lupus nephritis in 1) with concomitant cataract in 1, ILD in 2, hearing loss in 1 and finger amputation in 1). All 13 patients who survived are in remission. Ongoing maintenance treatment is Azatjioprine in 5, Mycophenolate mofetil in 3 and Rituximab in 3 patients. Conclusions: High index of suspicion with early diagnosis and treatment results in low mortality and better long term outcome. All mortality was because of delay in diagnosis. Rituximab is effective in achieving remission in refractory as well as relapsed cases References: Yi Lin, MD, et al. J Clin Rheumatol. 2009 Oct;15(7):341–4. Diffuse alveolar hemorrhage in systemic lupus erythematosus: risk factors and clinical outcome: results from affiliated hospitals of Catholic University of Korea2011 Jan;20(1):102–7. Alveolar haemorrhage in ANCA-associated vasculitides: 80 patients' features and prognostic factors. Kostianovsky A1.Clin Exp Rheumatol 2012 Jan-Feb;30(1 Suppl 70):S77–82. Disclosure of Interest: None declared